Pengaruh Analisis Kepuasan, Kemudahan, dan Kepercayaan Terhadap Minat Menggunakan Aplikasi Flip.id by Shifa Lailia - Atunnisa, Shifa Lailia Luluk; Handayani, Jati; Santosa, Teguh Budi (BanKu: Jurnal Perbankan dan Keuangan, 2023)
This study aims to analyse and obtain empirical evidence regarding the effect of satisfaction, convenience, and trust on interest in using the Flip.id application (study on Flip.id user Commercial Bank customers) both simultaneously and partially. The population in this study were all customers at Flip.id user Commercial Banks. The sampling technique used purposive sampling technique, as many as 100 respondents. The data used in this study are primary data obtained through distributing questionnaires. The data analysis model uses the Multiple Linear Regression Analysis Model. While the data analysis technique uses the F Statistical Test, the Coefficient of Determination (R2), and the t Statistical Test. The results of the analysis and discussion show that the variables of satisfaction, convenience, and trust simultaneously have a significant effect on interest in using the Flip.id application (Study on Commercial Bank customers who use Flip.id). Partially, the variables of satisfaction and trust each have a significant effect on the interest in using the Flip.id application (Study on Commercial Bank customers who use Flip.id) whereas, the convenience variable partially does not have a significant effect on the interest in using the Flip.id application (Study on Commercial Bank customers who use Flip.id).